2020
DOI: 10.1007/s00431-020-03663-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided supraclavicular cannulation of the brachiocephalic vein may reduce central line–associated bloodstream infection in preterm infants

Abstract: The objective of this study was to assess the risk of central line-associated bloodstream infection (CLABSI) of ultrasound (US)guided cannulation of the brachiocephalic vein (BCV) compared to standard epicutaneous cava catheters (ECCs) in preterm infants. This was a retrospective cohort study in preterm infants with a birth weight of less than 1500 g. Each BCV catheter was matched 1:3 with ECCs according to sex, birth weight, and year of insertion. The main outcome was the CLABSI density rate per 1000 days. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…9 While not commonly reported among our respondents, US can be used for subclavian access and has been demonstrated in adults to reduce complications. 12 Multiple small, singlecentered studies in pediatrics demonstrated high success rate reaching 100%, [13][14][15] with shorter procedure duration, 15 lower CLABSI rate, 16 and low to no major complications such as arterial puncture or pneumothorax. 11,15,17,18 Nonetheless, US use for subclavian placement is not routine for adult patients 19,20 and the pediatric data presented here are also consistent with that practice.…”
Section: Discussionmentioning
confidence: 99%
“…9 While not commonly reported among our respondents, US can be used for subclavian access and has been demonstrated in adults to reduce complications. 12 Multiple small, singlecentered studies in pediatrics demonstrated high success rate reaching 100%, [13][14][15] with shorter procedure duration, 15 lower CLABSI rate, 16 and low to no major complications such as arterial puncture or pneumothorax. 11,15,17,18 Nonetheless, US use for subclavian placement is not routine for adult patients 19,20 and the pediatric data presented here are also consistent with that practice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lumen size and blood flow of BCV are the largest among those available central veins, including IJV and SCV, 18 and the catheter-to-vein diameter ratio of the catheter (Babyport, 4.5F = 1.49 mm) and BCV (about 3.2 mm-diameter in infants) 9 is less than 45%, which has been considered as a protective factor for CRT. Moreover, the cannulation site of the catheter is located in the supraclavicular fossa, 17 which may alleviate patient discomfort at the neck, 7 reduce the risk for infection, 12,18 and maintain a smoother catheter curvature. 21 To our knowledge, no previous literature has evaluated using BCV approach for TIVAP placement in pediatric oncology population.…”
Section: Discussionmentioning
confidence: 99%
“…The IJV approach has disadvantages of higher puncture point, smaller catheter radian, risk of misplacement, catheter bending and blockage, and patient discomfort due to longer catheter trajectory 7 ; whereas the landmark SCV access is prone to be kinking such as pinch-off syndrome, and has a relatively lower success rate at first attempt and a higher intraoperative conversion rate to a secondary site. 8 However, since the initial report of ultrasound-guided brachiocephalic vein (BCV) approach in the supraclavicular region by Breschan et al 9 in 2011, it has been widely used in adults, 10 children, [11][12][13] infants, 14,15 and even premature infants [16][17][18] for central venous catheters' (CVCs) insertion procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their small size and narrow veins, most preterm neonates only tolerate the insertion of a single or double lumen central venous catheter (CVC) or peripherally inserted central catheter (PICC). Even though, the vascular access technology and culture has evolved, and jugular and brachiocephalic short and large catheters can be inserted under ultrasound guidance [ 1 3 ]. Limited venous access is a considerable challenge for the involved health care professionals when they have to administer several drugs, PN and blood transfusions intravenously and often together via the same catheter lumen [ 4 ].…”
Section: Introductionmentioning
confidence: 99%